Notice that the 2 expressions have 2 common terms.
(r-s) is just (s-r) times (-1)
similarly
(t-s) is just (s-t) times (-1)
this means that :
(r-s) (t-s) + (s-r) (s-t)=-(s-r)[-(s-t)]+(s-r) (s-t)
the 2 minuses in the first multiplication cancel each other so we have:
-(s-r)[-(s-t)]+(s-r) (s-t)=(s-r) (s-t)+(s-r) (s-t)=2(s-r) (s-t)
Answer:
d)<span>2(s-r) (t-s) </span>
Answer: x = 4, y = 3
<u>Step-by-step explanation:</u>
and
Using substitution method we get:
Answer:
Step-by-step explanation:
Step-by-step explanation:
Area of square
A = s²
A = 28²
A = 28 × 28
A = 784 cm²
To solve this, we use the formula for the volume of the frustum of a cone which is expressed as:
<span>V= (H/6)[WL + (W+a)(L+b) + ab]
</span>V = 3/6 [(6 ft. × 8 ft.) + (6 + 14)(18 + 8) + (<span>14 ft. × 18 ft.)]
</span>V = 409.98 ft^3 <-----OPTION C